Behaviors of Homologous Antibiotic Resistance Genes in a Cephalosporin WWTP, Subsequent WWTP and the Receiving River - Chen, Lei; Zhang, Mengyu; Ning, Daliang; Van Nostrand, Joy D; Yang, Yunfeng; Zhou, Jizhong; Zuo, Jiane (Frontiers in Environmental Science, 2021)
High concentrations of antibiotics in antibiotic production wastewater can cause the widespread transmission of antibiotic resistance genes (ARGs). Here, we collected a set of time series samples from a cephalosporin production wastewater treatment plant (X-WWTP), the subsequent municipal WWTP (Y-WWTP) and the receiving stream. Using a functional gene microarray, GeoChip 5.0, which contains multiple homologous probes for 18 ARG and 13 antibiotic metabolism gene (AMG) families, we found that more than 50% of homologous probes for 20 gene families showed a relative abundance higher in X-WWTP, while only 10% to 20% showed lower relative abundance. The different response patterns of homologous ARG (hARGs) within the same ARG family imply environmental selection pressures are only responsible for the ARG enrichment and spread of some specific instead of all ARG-containing microorganisms, which contradicted the traditionally held belief that environmental selection pressures, especially antibiotic concentration, select for all ARG-containing microorganisms thereby selecting different hARGs in the same ARG family in an undifferentiated way. Network results imply that hARGs from three β_lactamase families enriched under the selection pressure of high cephalosporin antibiotic concentrations in X-WWTP formed positively correlated homologous ARG clusters (pohARGCs). The pohARGCs were also enhanced in the sediment of the receiving stream. The enrichment of hARGs from three β_lactamase families was likely through microorganisms belonging to the Betaproteobacteria genus.